Relation between thickness, crystallite size and magnetoresistance of nanostructured La(1−)(x)Sr(x)Mn(y)O(3±δ) films for magnetic field sensors - Lukose, Rasuole (Beilstein J Nanotechnol, 2019)
In the present study the advantageous pulsed-injection metal organic chemical vapour deposition (PI-MOCVD) technique was used for the growth of nanostructured La(1−)(x)Sr(x)Mn(y)O(3±δ) (LSMO) films on ceramic Al(2)O(3) substrates. The compositional, structural and magnetoresistive properties of the nanostructured manganite were changed by variation of the processing conditions: precursor solution concentration, supply frequency and number of supply sources during the PI-MOCVD growth process. The results showed that the thick (≈400 nm) nanostructured LSMO films, grown using an additional supply source of precursor solution in an exponentially decreasing manner, exhibit the highest magnetoresistance and the lowest magnetoresistance anisotropy. The possibility to use these films for the development of magnetic field sensors operating at room temperature is discussed.